دراسة أثر الضوء والإشابة في عيّنات من السليسيوم اللابلوري المهدرج (Latakia University Journal -Basic Sciences Series, 2014)
تمت دراسة تركيز العيوب المتشكلة بالضوء من خلال دراسة انزياح سويّة فيرمي المقيس من تغير الناقلية مع درجة الحرارة لعينات من السليسيوم اللابلوري المهدرج , محضّرة بطريقة الترسيب الغازي المعزّز بالبلازما (Plasma Enhanced Chemical Vapor Deposition "PECVD"). بينت هذه الدراسة أن قيمة طاقة التنشيط للعيّنات في الحالة  As-depos. تشير إلى أنّ العينات قبل الإحماء (كما تكون عند استلامها من المخبر) تتعرض جزئياً للضوء خلال عملية النقل والتخزين. تم تفسير تأثر هذه العينات بالضوء على أنه عائد إلى قطع روابط ضعيفة من السليسيوم وتشكل روابط مقطوعة. وجدنا أيضاً أن العينات التي تحتوي على هيدروجين أقل هي الأكثر تأثراً بالضوء , ممّا يدلّ على دور الهيدروجين الهام في إشباع العيوب. كذلك تبيّن أن العينات التي تحتوي على الجرمانيوم بنسبة إشابة أقل هي الأكثر تأثراً بالضوء. We study the concentration of the defects created by the light from the measurement of the Fermi state displacement deduced from the conductivity variation with the temperature for samples of hydrogenated amorphous silicon (a-Si:H) deposited by Plasma Enhanced Chemical Vapor Deposition (PECVD). This study demonstrated that the value of the activation energy of the samples in the case of As-depos. indicate that the samples before the warm-up (as are upon receipt of these samples from the laboratory) partially exposed to light during the process of transportation and storage. Been explained the effect of light on this samples that it was returning to cut weak silicon bonds and then the creation of new dangling bonds. We also found that the samples containing less hydrogen are the most affected by the light which indicates the important role of hydrogen in the satisfaction of defects. Also found that samples which contain germanium by less dopant are most affected by light.